2018
DOI: 10.1016/j.ymthe.2018.01.018
|View full text |Cite
|
Sign up to set email alerts
|

The Neurotropic Properties of AAV-PHP.B Are Limited to C57BL/6J Mice

Abstract: Improved delivery of adeno-associated virus (AAV) vectors to the CNS will greatly enhance their clinical utility. Selection of AAV9 variants in a mouse model led to the isolation of a capsid called PHP.B, which resulted in remarkable transduction of the CNS following intravenous infusion. However, we now show here that this enhanced CNS tropism is restricted to the model in which it was selected, i.e., a Cre transgenic mouse in a C57BL/6J background, and was not found in nonhuman primates or the other commonly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

12
329
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 338 publications
(343 citation statements)
references
References 12 publications
12
329
2
Order By: Relevance
“…Another example, where results from rodent studies do not translate directly to studies with large animal models, is the recent observation that high doses (2e14 GC/kg) of rAAV9 vectors can lead to severe acute toxicity in piglets and non-human primates when delivered intravenously [91,92]. In this case, and different from the trial results reported by Manno et al [59], the toxicity was likely due to an acute, innate immune response (around 5 days after vector administration).…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…Another example, where results from rodent studies do not translate directly to studies with large animal models, is the recent observation that high doses (2e14 GC/kg) of rAAV9 vectors can lead to severe acute toxicity in piglets and non-human primates when delivered intravenously [91,92]. In this case, and different from the trial results reported by Manno et al [59], the toxicity was likely due to an acute, innate immune response (around 5 days after vector administration).…”
Section: Lessons Learned From Ex-vivo Successmentioning
confidence: 99%
“…26 These promising achievements may allow the administration of reduced dose of vector for a similar efficacy; this may address recent concerns over possible doselimited toxicity of AAV9-derived capsids. 27,28 Fetal gene therapy has remained an elusive goal for decades. This proof of concept study highlights long-term efficacy and technical feasibility of this approach.…”
mentioning
confidence: 99%
“…Interestingly, this receptor is not conserved in primates and humans, thus implying species-specific difference in the transduction efficacy of these capsids. On this line, new findings indicate that brain transduction in adult primates is not improved with PHP.B compared to AAV9 although only few animals have yet been tested 38,39 . Nonetheless, the PHP.B/eB receptor belongs to the large family of Ly6/uPar proteins, some of which are conserved in mammalian evolution and can be found in human brain endothelium, representing valuable targets for capsid engineering 40,41 .…”
Section: Discussionmentioning
confidence: 99%